2018
DOI: 10.3389/fchem.2018.00032
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Fast Pyrolysis of Biomass Impregnated with Potassium Phosphate in a Hydrogen Atmosphere for the Production of Phenol and Activated Carbon

Abstract: A new technique was proposed to co-produce phenol and activated carbon (AC) from catalytic fast pyrolysis of biomass impregnated with K3PO4 in a hydrogen atmosphere, followed by activation of the pyrolytic solid residues. Lab-scale catalytic fast pyrolysis experiments were performed to quantitatively determine the pyrolytic product distribution, as well as to investigate the effects of several factors on the phenol production, including pyrolysis atmosphere, catalyst type, biomass type, catalytic pyrolysis tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Besides, during the pyrolysis, NH 4 H 2 PO 4 could act as a donor of hydrogen for biomass (Zeng and Bernstein, 2019). As confirmed in previous literatures (Lu et al, 2018c;Zhang et al, 2019), the hydrogen source would exhibit positive effects on the formation of phenol by removing the substitutes on the aromatic rings. Furthermore, the co-pyrolysis of NH 4 H 2 PO 4 and poplar could generate abundant P-containing functional groups, like -O-P-C-, -C-P=O, and so on (Zhang et al, 2018b), which could improve the formation of phenol from non-lignin constituents, viz.…”
Section: Pyrolysis Of Poplar Impregnated With Nh 4 H 2 Pomentioning
confidence: 52%
See 1 more Smart Citation
“…Besides, during the pyrolysis, NH 4 H 2 PO 4 could act as a donor of hydrogen for biomass (Zeng and Bernstein, 2019). As confirmed in previous literatures (Lu et al, 2018c;Zhang et al, 2019), the hydrogen source would exhibit positive effects on the formation of phenol by removing the substitutes on the aromatic rings. Furthermore, the co-pyrolysis of NH 4 H 2 PO 4 and poplar could generate abundant P-containing functional groups, like -O-P-C-, -C-P=O, and so on (Zhang et al, 2018b), which could improve the formation of phenol from non-lignin constituents, viz.…”
Section: Pyrolysis Of Poplar Impregnated With Nh 4 H 2 Pomentioning
confidence: 52%
“…Currently, only limited researches have been performed on the selective preparation of phenol. Our group put forward a creative method to obtain phenol from catalytic decomposition of biomass by impregnation of K 3 PO 4 or blended with magnetic K 3 PO 4 /Fe 3 O 4 solid catalyst under hydrogen atmosphere (Lu et al, 2018c;Zhang et al, 2019). The phenol yields reached 5.3 and 4.3 wt%, respectively, both with excellent selectivity of ∼18%.…”
Section: Introductionmentioning
confidence: 99%
“…16 In the case of gas-phase reactions, conversion products are often collected in gas bags prior to analysis or condensed in liquid traps, which may complicate the analysis of original species. 11,17,18 In response, on-line GC−MS has been developed. It was recently used to study the conversion of furan over zeolites, and several HC products were identified and quantified.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Furthermore, light gases such as water and C 1 –C 3 species might not be routinely analyzed . In the case of gas-phase reactions, conversion products are often collected in gas bags prior to analysis or condensed in liquid traps, which may complicate the analysis of original species. ,, In response, on-line GC–MS has been developed. It was recently used to study the conversion of furan over zeolites, and several HC products were identified and quantified. ,, Despite the on-line approach, the demonstrated time resolution was at best limited to several minutes.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies were conducted to compare the emission of carbon monoxide, carbon dioxide, nitrogen oxides, and methane as well as the energy released from combustion and the combustion efficiency. All the experiments were carried out at different heating rates (20,25,30, and 40 o C/min) and airflow rates (30, 50, 80 and 100 ml/min), with temperatures ranging from 50-800 o C. The difference in reactivities was quantified at different conversion levels of the solid fuels in terms of activation energies, and preexponential factors. This study expands on our previous work [31] in which catalyst impregnation was done on charcoal but the experiments were done isothermally in a tube furnace, yet real-life combustion occurs non-isothermally.…”
Section: Introductionmentioning
confidence: 99%